Epidemiological Profile of Dengue Fever Cases in Azad Jammu & Kashmir, Pakistan - Rehman, Syed Nadeem-ur-; Hafeez, Uzma; Gafoor, Tamkeen; Rana, Asghar (International Journal of Pathology, 2018)
Background: The first outbreak of Dengue fever was reported in State of Azad Jammu & Kashmir (AJ&K) in 2016.Objective: This study was carried out to assess the magnitude of dengue fever and its description with respect to socio demographic and clinical characteristics during 2016 in AJ& K.Methodology: This descriptive study was carried out on secondary data received at the Directorate of Communicable Diseases Control (CDC) Muzaffarabad. A case was defined as “any resident of state of AJ&K, presenting with fever and having any two of the symptoms; Headache, retro-orbital pain, myalgia, arthralgia, nausea, vomiting, abdominal pain and bleeding, and found positive on screening with Immune chromatographic IgM/IgG rapid test or NS1Ag from 1st January 2016 to 31st December, 2016”. Data was analyzed by person place and time and frequencies proportions and rates were calculated.Results: A total of 388 cases were recorded in which 61.85% (n=240) were males. Majority of the cases (98.7%) were reported from district Muzaffarabad. The median age of cases was 30 years (range 4-72 yrs). Majority of cases (78%) were below 40 years. The attack rate was heigiest in age group 20-29 years(25/100,000 population) The Epi-curve showed that index case was reported on 21st August 2016.Multiple peaks were noted thereafter & epidemic subsided in November 2016. Fever was associated with headache (90%), myalgia (86%), retro-orbital pain (60%), nausea (51%) vomiting (45%) abdominal pain (38%) arthralgia (35%) and rash (20%) of the cases. Diagnosis was made on NS1 in 30% & IgM serology in 70% of the cases. Mortality rate was zero and recovery rate was 100%.Conclusions: Majority of cases were males below 40 years. Headache, retro-orbital pain and myalgia were commonly associated symptom with fever in dengue patients and all cases recovered fully with treatment. Dengue surveillance and community awareness regarding its prevention are keys to keep it under control in AJ&K.